1997
DOI: 10.1006/brln.1997.1795
|View full text |Cite
|
Sign up to set email alerts
|

Tense and Agreement in Agrammatic Production: Pruning the Syntactic Tree

Abstract: This paper discusses the description of agrammatic production focusing on the verbal inflectional morphology. Agrammatism in Hebrew is investigated through an experiment with a patient who displays a highly selective impairment: agreement inflection is completely intact, but tense inflection, use of copula, and embedded structures are severely impaired. A retrospective examination of the literature shows that our findings are corroborated by others. A selective account of the agrammatic production deficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
339
9
29

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(404 citation statements)
references
References 30 publications
27
339
9
29
Order By: Relevance
“…This implied, according to the authors, that the basic problem was a syntactic one, not a morphological or lexical one. These findings are compatible with theories on functional projection in aphasia, like the ones from Hagiwara (1995) and Friedmann and Grodzinsky (1997); Positions high in the syntactic tree are difficult to realize for agrammatic speakers.…”
Section: The Relation Between Verb Inflection and Verb Position In Brsupporting
confidence: 89%
See 1 more Smart Citation
“…This implied, according to the authors, that the basic problem was a syntactic one, not a morphological or lexical one. These findings are compatible with theories on functional projection in aphasia, like the ones from Hagiwara (1995) and Friedmann and Grodzinsky (1997); Positions high in the syntactic tree are difficult to realize for agrammatic speakers.…”
Section: The Relation Between Verb Inflection and Verb Position In Brsupporting
confidence: 89%
“…Most studies on the grammatical aspects of verb production in Broca's aphasia have been done in English, which is not the most suitable language for such research because the inflectional paradigm is very limited and there is little variation in the position of the verb. When one looks at verb production in sentence context in other languages such as Hebrew (Friedmann, 2000;Friedmann & Grodzinsky, 1997) or Hungarian (Kiss, 2000), interesting patterns emerge. Friedmann and Grodzinsky (1997) and Friedmann (2000) showed that Hebrew agrammatics make more errors with inflection for tense than with inflection for agreement, and Kiss (2000) showed that in Hungarian the amount of grammatical information that the verb contains influences the ability to produce it in sentence context; the more grammatical roles belong to the verb and the more morphological information, the more difficult it is to retrieve the verb in sentence context.…”
Section: Introductionmentioning
confidence: 99%
“…Given that agrammatic aphasic individuals often produce syntactically ill-formed speech, it has been proposed that verb inflection errors in agrammatism occur because syntactic wellformedness constraints are rendered inaccessible (Arabatzi & Edwards, 2002; Tree-Pruning Hypothesis (TPH) : Friedmann & Grodzinsky, 1997). Previous syntactic accounts are based on the observation that agreement morphology seems to be better preserved than tense morphology in agrammatic aphasia, and have suggested that tense nodes are inaccessible to the checking mechanism, while agreement nodes are accessible (Friedmann & Grodzinsky, 1997), or that tense is underspecified (Tense Underspecification Hypothesis (TUH): Wenzlaff & Clahsen, 2004).…”
mentioning
confidence: 99%
“…It has been shown that agrammatic aphasic speakers use a reduced proportion of finite verbs (see, e.g., Bastiaanse, Rispens, & Van Zonneveld, 1999;Friedmann & Grodzinsky, 1997;Hagiwara, 1995). The same has been observed in normally developing children and children with specific language impairment (SLI), in that they produce a relatively larger number of so-called optional infinitives than finite verbs (e.g., Wexler, Schaeffer, & Bol, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…In the literature it has often been suggested that both populations suffer from a grammatical deficit (for agrammatism, see, for example, Hagiwara, 1995;Friedmann & Grodzinsky, 1997;Bastiaanse & Van Zonneveld, 1998; for SLI, see Rice & Wexler, 1996). At the same time we know that agrammatic aphasics have problems accessing verbs (see, for example, Thompson, Lange, Schneider, & Shapiro, 1997;Bastiaanse & Jonkers, 1998).…”
Section: Individual Datamentioning
confidence: 99%